(untitled) (Vietnam Journal of Community Medicine, 2026)
Background: Unintentional injuries are a leading cause of mortality in children, necessitating timely and correct first aid intervention from parents. This study aimed to assess the current status of initial first aid knowledge and associated factors among parents within the Vinschool preschool system. Methods: A cross-sectional descriptive study was conducted on 207 parents with children attending three Vinschool preschool campuses in Hanoi. Results: The proportion of parents with satisfactory knowledge was 72.9%. Knowledge regarding head injury management (99.0%) and burns (94.2%) was highest, while the ability to recognize signs of cardiac arrest was lowest (49.3%). Males had a 4.3 times higher risk of having unsatisfactory knowledge compared to females (OR=4.30; 95%CI: 1.85–10.02); those who had never received training had a 6.96 times higher risk of unsatisfactory knowledge compared to the trained group (OR=6.96; 95%CI: 1.21–51.30). Conclusion: Parental first aid knowledge was generally good but uneven across specific skills and genders. Practical training courses at schools should be promoted, prioritizing males and those who have never received prior training.